Pengaruh Profitabilitas, Leverage, Likuiditas dan Kepemilikan Institusional terhadap Pengungkapan Corporate Social Responsibility: (Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2023) - Indira Nahdaffa Rahma; Suryani Suryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of the research is to find the influence of variables Profitability, Leverage, Liquidity and Institutional Ownership on Corporate Social Responsibility Disclosure. The sample in this study includes 33 companies sub-sector food and beverage listed in Indonesia Stock Exchange (BEI) in the period 2019-2023. The sampling technique used purposive sampling method and obtained 165 sample data from 33 companies. The analytical tool used is multiple linear regression analysis using the Statistical Prosuct and Service Solution (SPSS) Version 22 program. The result of this study indicate that Profitability has a significant possitive effect on Corporate Social Responsibility Disclosure, Leverage have no significant effect on Corporate Social Responsibility Disclosure, Liquidity have no significant effect on Corporate Social Responsibility Disclosure and Institutional Ownership has a significant possitive effect on Corporate Social Responsibility Disclosure.